2022
DOI: 10.3390/educsci12060404
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Attitudes towards Inclusive Education at Greek Secondary Education Schools

Abstract: Advocates of inclusive education believe in the right of all learners to education and the many benefits it delivers. Teachers’ attitudes and beliefs toward inclusive education are instantly reflected in their classroom activities and practices. This research will concentrate on special and general education teachers in Greek secondary schools. It will investigate their attitudes toward inclusive education and how these attitudes alter as a consequence of variables such as age, gender, teaching experience, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
2
14
2
1
Order By: Relevance
“…Also, the low SACIE-R reliabilities could constitute limitations to our study. However, some researchers (Mouchritsa, Romero and Garay et al, 2022;Nasir, 2019) have reported similar reliabilities indicating that this is not specifically a problem with our data. It may be a more general issue of the scale itself.…”
Section: Conclusion Implications and Limitationssupporting
confidence: 75%
“…Also, the low SACIE-R reliabilities could constitute limitations to our study. However, some researchers (Mouchritsa, Romero and Garay et al, 2022;Nasir, 2019) have reported similar reliabilities indicating that this is not specifically a problem with our data. It may be a more general issue of the scale itself.…”
Section: Conclusion Implications and Limitationssupporting
confidence: 75%
“…According to Forlin et al (2011) , the calculation of Cronbach’s alpha indicated good internal reliability for the 15-item of the scale ( α = 0.74) and all three factors ( α = 0.75, α = 0.67, α = 0.65 for sentiments, attitudes, and concerns, respectively). The SACIE-R instrument has been used in various countries, such as Bahrain ( AlMahdi and Bukamal, 2019 ), Australia ( McCracken et al, 2020 ), Ghana ( Opoku et al, 2021 ), and Greece ( Mouchritsa et al, 2022 ). As the participants in the current study spoke only Arabic, the SACIE-R was translated from English into Arabic by four bilingual (Arabic and English) special education and PE professors using the bilingual method ( Brislin, 1970 ).…”
Section: Methodsmentioning
confidence: 99%
“…More positive teacher attitudes towards inclusiveness tend to raise productivity, influence special education students' behaviour, performance and academic achievement (Benkohila et al., 2020), and affect practice and policy decisions (Alzyoudi et al., 2022). Their support is therefore critical to the success of inclusion (Alzyoudi et al., 2022; Fakolade & Adeniyi, 2009; Mouchritsa et al., 2022; Politou, 2022). Teachers must thus identify their attitudes towards students with disabilities so as not to disrupt the latter's work and the success of inclusion (Alabdallat et al., 2021; Mezquita‐Hoyos et al., 2018; Parker, 2009).…”
Section: Effects Of Teachers' Attitudes Towards Inclusionmentioning
confidence: 99%
“…According to Mouchritsa et al. (2022), of 307 educators, females supported inclusive education more than males, and were almost equally divided between general and special education.…”
Section: Special Education Teachers' Attitudes Towards Inclusionmentioning
confidence: 99%
See 1 more Smart Citation